Integrasi Iman, Islam, dan Ihsan: Sebuah Pendekatan Tafsir Tematik dan Tadabbur Al-Qur'an: Penelitian - Khalim, Nor (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to explore the integration of the concepts of Iman, Islam, and Ihsan as an organic unity in shaping a holistic Muslim personality (Insan Kamil) and its relevance to mental health in the modern era. Employing a qualitative library research method with a thematic interpretation approach (tafsir maudhu’i), this study analyzes primary data from Qur'anic verses and authoritative tafsir texts, as well as secondary literature related to Islamic psychology. The results indicate that Ihsan is not merely ethics, but the pinnacle of spirituality that complements the foundation of Iman and Islamic Sharia. Through the Tadabbur Al-Qur'an method, these values are internalized to transform cognitive knowledge into firm conviction (haqqul yaqin) and awareness of Divine supervision (muraqabah). This study concludes that the synergy of these three pillars serves as an effective preventive and curative mechanism in addressing existential crises and mental disorders, such as anxiety and stress, amidst the challenges of the digital era and Society 5.0.